Modeling of Bau-Lundu trunk water main by using epanet software - Bellgalmano, Low. (Universiti Malaysia Sarawak (UNIMAS), 2012)
the increase in number of populations with an improved standard of living in communities and the affects of extensive land use particularly in gravity feed water system catchment areas have caused a tremendous increase in level of demand for treated water in rural areas. Thus, a precise decisison to embark for the upgrading of the existing or construction of new water supply infrastructures to meet the growing need and future demand has become an essential requirement for water supply agencies. further augmentation of treated water from source of sufficient supply can be achieved through expansion of existing distribution network by upgrading or installation of new water main.